2005
DOI: 10.1117/12.615717
|View full text |Cite
|
Sign up to set email alerts
|

Estimating growth status of winter wheat based on aerial images and hyperspectral data

Abstract: The aim of this paper is to estimate the growth status and yield of winter wheat using aerial images and hyperspectral data obtained by unmanned aircraft, and then to perform precision management to the crop. The test farm was divided into 48 cells. Twenty-four cells were selected as variable rate fertilization area, and the other 24 cells were used as contrast area with low fertilization in growth season. In 2004, the aerial images of winter wheat canopy were measured from an unmanned aircraft. The SPAD value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In all cases, the errors represent a high percentage of nutrient variability in the field, making them ineffective. This analysis explains the discrepancy and helps in understanding the results of other authors and studies where the effects of using N-Tester were identified, but not in the expected magnitude (Han et al 2005;Liang et al 2004).…”
Section: Study Of the N-tester Reading In The Field Hajmentioning
confidence: 69%
“…In all cases, the errors represent a high percentage of nutrient variability in the field, making them ineffective. This analysis explains the discrepancy and helps in understanding the results of other authors and studies where the effects of using N-Tester were identified, but not in the expected magnitude (Han et al 2005;Liang et al 2004).…”
Section: Study Of the N-tester Reading In The Field Hajmentioning
confidence: 69%
“…Dammer et al (2015) applied NDVI (Normalised Difference Vegetation Index) to distinguish between wheat varieties with varying levels of resistance to Fusarium spp. Han et al (2005) obtained images from the UAS system for evaluation of the growth status of winter wheat. In crop monitoring, aerial imaging has an advantage over collecting data by means of small-scale satellite remote-sensing as well as by sensors mounted on ground-operating machines: the highresolution images taken from a relatively small height and at favourable atmospheric conditions provide a good insight into details and, at the same time, the general overview of the cultivated area (Bzowska-Bakalarz et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Dammer et al (2015) applied NDVI (Normalised Difference Vegetation Index) to distinguish between wheat varieties with varying levels of resistance to Fusarium spp. Han et al (2005) obtained images from the UAS system for evaluation of the growth status of winter wheat. In crop monitoring, aerial imaging has an advantage over collecting data by means of small-scale satellite remote-sensing as well as by sensors mounted on ground-operating machines: the highresolution images taken from a relatively small height and at favourable atmospheric conditions provide a good insight into details and, at the same time, the general overview of the cultivated area (Bzowska-Bakalarz et al 2017, Lan et al 2010.…”
Section: Introductionmentioning
confidence: 99%